1996
DOI: 10.1016/0925-4773(95)00464-5
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic expression of glial cell-line derived neurotrophic factor (GDNF) suggests multiple developmental roles in neural differentiation and epithelial-mesenchymal interactions

Abstract: We describe the cloning of the mouse glial cell line-derived neurotrophic factor (GDNF) gene and its expression during embryogenesis. GDNF is a distant member of the superfamily of TGF-beta related genes that was originally identified on the basis of its striking neurotrophic activity. GDNF is expressed in a highly dynamic pattern in the anterior neuroectoderm during early stages of neurogenesis between E7.5 and E10.5. Beginning at E10.5 GDNF is also expressed in several organs that develop through inductive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(127 citation statements)
references
References 33 publications
5
121
0
Order By: Relevance
“…GDNF7/7 mice have similar phenotypic characteristics to their RET7/7 counterparts: kidney agenesis or severe dysgenesis and absence of the enteric ganglia (Sa nchez et al, 1996;Moore et al, 1996;Pichel et al, 1996). Consistent with RET's proposed role as a transducer of mesenchyme-derived signals in kidney induction, GDNF expression has been localized to the metanephric mesenchyme (Hellmich et al, 1996).…”
Section: Introductionmentioning
confidence: 71%
“…GDNF7/7 mice have similar phenotypic characteristics to their RET7/7 counterparts: kidney agenesis or severe dysgenesis and absence of the enteric ganglia (Sa nchez et al, 1996;Moore et al, 1996;Pichel et al, 1996). Consistent with RET's proposed role as a transducer of mesenchyme-derived signals in kidney induction, GDNF expression has been localized to the metanephric mesenchyme (Hellmich et al, 1996).…”
Section: Introductionmentioning
confidence: 71%
“…Our understanding of the mammalian spermatogonial stem cell niche has recently greatly progressed with the discovery that glial cell line-derived neurotrophic factor (Gdnf), a neurotropic factor secreted by glial cells in the brain, is also expressed in other organs during development, including ovary and testis Hellmich et al, 1996;Trupp et al, 1995;Golden et al, 1999). Gdnf, secreted by Sertoli cells after birth, is so far the only known paracrine factor in the testis specifically responsible for the maintenance and selfrenewal of SSCs in vivo and in vitro (Meng et al, 2000;Kubota et al, 2004b;Hofmann et al, 2005b).…”
Section: Spermatogenesis and The Spermatogonial Stem Cell Nichementioning
confidence: 99%
“…Because it improves motor functions in animal models of parkinsonism, Gdnf has been seen as a promising therapy for Parkinson disease (Grondin and Gash, 1998). The role of Gdnf in embryonic development is not limited to the nervous system and it is also essential for kidney and gastrointestinal tract formation (Schuchardt et al, 1994;Moore et al, 1996;Hellmich et al, 1996). Cloning of Gdnf revealed that it is a distant member of the transforming growth factor beta (Tgf-β) superfamily (Lin et al, 1993).…”
Section: Role Of Gdnf In the Mammalian Testismentioning
confidence: 99%
“…EGCs could therefore contribute to the development of the enteric neuronal network (Bä r et al, 1997;Gershon, 1999) and to neuroprotection. However, EGCs are not the primary source of GDNF in the developing gut as GDNF is expressed as early as E9.0 in the mouse gut (Hellmich et al, 1996), although differentiated EGCs first appear at E16 (Rothman et al, 1986).…”
Section: Neuroprotective and Neuromodulatory Functions Of Egcmentioning
confidence: 99%